2011
DOI: 10.1037/a0024407
|View full text |Cite
|
Sign up to set email alerts
|

Suspicious spirits, flexible minds: When distrust enhances creativity.

Abstract: Intuitively, as well as in light of prior research, distrust and creativity appear incompatible. The social consequences of distrust include reluctance to share information, a quality detrimental to creativity in social settings. At the same time, the cognitive concomitants of distrust bear resemblance to creative cognition: Distrust seems to foster thinking about nonobvious alternatives to potentially deceptive appearances. These cognitive underpinnings of distrust hold the provocative implication that distru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 188 publications
(463 reference statements)
4
98
0
3
Order By: Relevance
“…For example, exposure to a given concept (e.g., "temporary") usually facilitates the subsequent identification of related congruent concepts (e.g., "transitory"); yet, distrust reverses this effect and facilitates the identification of conceptincongruent terms (e.g., "permanent"; Schul et al, 2004). Moreover, people in a distrustful mindset are more likely to entertain alternative interpretations of utterances (Fein, 1996; A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT SUSPICION & COGNITIVE PROCESSING 5 Burnstein, & Bardi, 1996) and to generate more unusual solutions on creativity tasks (Mayer & Mussweiler, 2011). Furthermore, Mayo, Alfasi, and Schwarz (2014) reported that distrust improves performance on Wason's (1960) rule discovery task by increasing the prevalence of negative hypothesis testing.…”
Section: Distrust and Its Cognitive Consequencesmentioning
confidence: 94%
“…For example, exposure to a given concept (e.g., "temporary") usually facilitates the subsequent identification of related congruent concepts (e.g., "transitory"); yet, distrust reverses this effect and facilitates the identification of conceptincongruent terms (e.g., "permanent"; Schul et al, 2004). Moreover, people in a distrustful mindset are more likely to entertain alternative interpretations of utterances (Fein, 1996; A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT SUSPICION & COGNITIVE PROCESSING 5 Burnstein, & Bardi, 1996) and to generate more unusual solutions on creativity tasks (Mayer & Mussweiler, 2011). Furthermore, Mayo, Alfasi, and Schwarz (2014) reported that distrust improves performance on Wason's (1960) rule discovery task by increasing the prevalence of negative hypothesis testing.…”
Section: Distrust and Its Cognitive Consequencesmentioning
confidence: 94%
“…Also being exposed to trust-vs. suspicion-evoking information in one context may influence how one processes information in another, unrelated context (e.g. Mayer & Mussweiler, 2011;Schul, Mayo, & Burnstein, 2008;Schul et al, 2004). Thus, according to social psychological theorizing and research, reflective trust judgments and trust decisions should clearly be influenced by contents that have been activated in a previous, unrelated task and still exert their influence in the associative structures of the impulsive system.…”
Section: Introductionmentioning
confidence: 98%
“…For example, words with a hostile connotation biased subjects' ratings of other persons' personality towards more hostile scores (Smith & Branscombe, 1988), words expressing distrust increased subjects' creativity (Mayer & Mussweiler, 2011) and words denoting narrowness or wideness narrowed or widened, respectively, subjects' focus of attention (Hüttermann, Memmert, & Bock, 2012). Conceptual priming doesn't require awareness as it was found with subliminally presented targets (Hüttermann et al, 2012) and in completely amnestic patients (Levy, Stark, & Squire, 2004).…”
Section: Introductionmentioning
confidence: 84%